Fibrinogen-modified sodium alginate as a scaffold material for skin tissue engineering. (24th January 2018) - Solovieva, Elena V; Fedotov, Alexander Yu; Mamonov, Vasily E; Komlev, Vladimir S; Panteleyev, Andrey A
Abstract: In search for a new pro-angiogenic scaffold material suitable for skin bioengineering and grafting therapy, we have fabricated a number of composite sodium alginate (AG)–fibrinogen (FG) sponge scaffolds using the freeze-drying approach. Thrombin was added to drive FG/fibrin conversion, while ε -aminocapronic acid ( ε Ac) was used as antifibrinolytic component. The slow rates of scaffold biodegradation were achieved by using Ca 2+ and Mg 2+ cations as cross-linking agents. The novel thrombin-modified AG–FG scaffolds with highly interconnected porous structure were evaluated using scanning electron microscopy, tensile testing and pycnometric analysis. The scaffolds were characterized by high porosity and tensile strength, possessing average pore size from about 60 to 300 μ m depending on AG/FG ratio and fibrin stabilization. The biocompatibility of thrombin-modified scaffolds with a different AG/FG ratio was tested on human cells with potential applicability to skin tissue engineering: immortalized epidermal keratinocytes (N-TERT), primary skin fibroblasts, endothelial cells (HUVEC) and subcutaneous adipose-derived stromal cells. The scaffolds with low (15%) FG content have shown the highest adhesiveness and survival rates for all types of cells, as compared to the scaffolds with higher FG content. In unstabilized scaffolds, the addition of FG did not stimulate the aortic ring sprouting. At the same time, fibrin stabilization by ε Ac resulted in significant increase of aortic ring sprouting and more efficient formation of microvascular network. Altogether, obtained results suggest that thrombin-modified alginate sponges can be successfully used as a grafting material by itself to promote skin healing and regeneration and also as a scaffold for three-dimensional bioequivalent construction.